Identifying repeat victimization with GIS - Ratcliffe, Jerry (The British journal of criminology, 1998)
Until recently most attempts at identifying repeat victimization locations have focused on searching address fields in police records. Problem with inaccurate data entry and variation in address format make this method fraught with difficulty and time consuming to correct. This study of burglary suggests that a standard GIS package, searching geo-referenced crime locations can dramatically improve the time and accuracy of identifying repeats. The research presented here appears generally consistent with other published work in that the period of highest risk is immediately after an initial burglary. The study covers a longer period than usual. Two years' worth of data raises issues regarding definitions of repeat victimization